Application oriented material characterisation and simulation for adsorption thermal energy storage - Schmit, Henri; Pöllinger, Simon; Schubert, Tobias; Lävemann, Eberhard; Hiebler, Stefan (Frontiers in Thermal Engineering, 2025)
Thermal energy storage based on adsorption and desorption of water on zeolites promises high energy storage densities. In the design of adsorption thermal energy storages, an application oriented material characterisation and simulation is necessary to choose an adsorbent that is a good match for the application conditions. Therefore, a method consisting of four steps is proposed. In the first step, potential adsorbents are compared to each other under application conditions using characteristic curves. The equilibrium data to determine the characteristic curves of commercially available CWK 13XBFK and NaYBFK is measured via a simultaneous thermal analysis (STA) device used in thermogravimetric analysis (TGA) mode and a coupled humidity generator. The characteristic curves of CWK 13XBFK and NaYBFK are successfully determined for adsorption potentials ΔF between 105 kJ kg-1 ≤ ΔF ≤ 3,495 kJ kg-1 and 106 kJ kg-1 ≤ ΔF ≤ 3,524 kJ kg-1, respectively. In both investigated scenarios of a mobile sorption storage and a industrial tumble dryer, CWK NaYBFK has a slightly higher volumetric water uptake than 13XBFK. In the second step, breakthrough curves are recorded for both zeolites under adsorption and desorption conditions for a mobile sorption storage. The results indicate that the desorption conditions are a better match for CWK NaYBFK while the adsorption conditions are a better match for CWK 13XBFK. In the third step, the experimental breakthrough curves serve to validate a fixed bed simulation that can be used to construct a sorption system for the investigated adsorption and desorption conditions. In the fourth and last step, both zeolites are cycled for 140 cycles between a temperature of 300 °C and dew point temperature of 60°C for desorption and a temperature of 42.5°C and 30 °C for adsorption. These conditions based on the integration of a sorption system into an industrial tumble dryer lead to a decrease of the water adsorption capacity of 36.5% for CWK 13XBFK and 3.3% for CWK NaYBFK.